Queer Lives Across the Wall : Desire and Danger in Divided Berlin, 1945-1970. - Rottmann, Andrea. (German and European Studies, 2023)
Queer Lives across the Wall draws on personal letters, photo albums, and state records in order to tell the history of East and West Berlin in the early Cold War through an LGBTIQ* perspective.